Pengaruh Likuiditas Dan Inventory Intensity Terhadap Agresivitas Pajak Dengan Manajemen Laba Sebagai Variabel Pemoderasi Pada Perusahaan Lq45 - Miladiah Kusumaningarti; Rike Selviasari; Fitria Nur Wahyuningsih (Jurnal Riset Akuntansi, 2023)
The purpose of this study was to determine the effect of liquidity (X1) and inventory intensity (X2) on tax aggressiveness (Y) with earnings management (Z) as a moderating variable in LQ45 companies for the 2019-2021 period. The population in this study is the financial statements of LQ45 companies for the 2019-2021 period. 2019 – 2021. The population of this study were 45 companies and 28 companies were selected as sample criteria in purposive sampling. The analysis technique used in this study is multiple analysis techniques and moderated regression analysis which is tested with the classical assumption test. The results of this study indicate that liquidity and inventory intensity have no effect on tax aggressiveness. In addition, the results of research on moderating variables with earnings management weaken the effect of liquidity on tax aggressiveness and the effect of inventory intensity weakens tax aggressiveness